EXTRACTION AND EVALUATION OF NIGELLA SATIVA AND SYZYGIUM AROMATICUM OILS AND THEIR PHARMACOLOGICAL STANDARDIZATION - Praful Kumar; Asif Raza; Rajnish Kumar Rana; Satyam Prasad; Avinash Kumar Ray; Syed Mohammad Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Nigella sativa (black seed) and Syzygium aromaticum (clove) have been widely recognized for their medicinal and pharmacological significance, primarily due to their bioactive compounds—thymoquinone and eugenol, respectively. This study focused on the extraction of essential oils by using the cold compression method and to evaluates their antioxidant, anti-inflammatory, and antimicrobial activities. The antimicrobial efficacy of the both extracted oils were assessed against common pathogenic microorganisms including both Gram-positive and Gram-negative bacterial strains against standardized antimicrobial testing methods. The results indicated that both the study samples (oils) exhibited notable antimicrobial properties along with promising antioxidant and anti-inflammatory activities. In addition, both reinforcing the antimicrobial potential as natural therapeutic agents. Standardization processes were conducted to ensure consistency, potency, and safety, to establish their viability for pharmaceutical applications. This research underscores the potential of Nigella sativa and Syzygium aromaticum oils as an effective alternative to synthetic antimicrobial agents, contributing to advancements in natural medicine.